A LITERATURE REVIEW AND CLASSIFICATION OF ENTERPRISE SOFTWARE SELECTION APPROACHES - Sen, Ceyda Guengoer; Baracli, Hayri; Sen, Selcuk (WORLD SCIENTIFIC PUBL CO PTE LTD, 2009)
The evaluation and selection of enterprise software has become increasingly difficult for decision makers due to a large number of software products available for many applications. Therefore, systematic and repeatable approaches are needed in order to select the appropriate product that best meets the customer requirements. In this paper, we present a literature review and classification of enterprise software selection approaches from the period 1982-2007. In addition to classifying the selected approaches by functional perspective, the decision-making methods used by these approaches in the generic phases of software selection process are also presented. Results are summarized with comprehensive classification tables. This study is intended as a source for academics and practitioners alike interested in software selection problem, especially those who want to see alternative decision-making techniques that can be used to support the every single step of software selection process.
Keywords: Enterprise software; software selection approaches; functional classification; decision-making methods; literature review; DECISION-MAKING; MULTIPLE; METHODOLOGY; FRAMEWORK; CRITERIA; QUALITY; MODEL; COST; AHP; Computer Science; Operations Research & Management Science